Elaine Steinbeck standing in front of their new Range Rover. - unknown:::Creator:::::::::::: (United States; Sag Harbor, New York, 2022)
John and Elaine Steinbeck at a beach picnic with Daga Ramsey and other friends. Elaine stands in front of Steinbeck's new four-wheel-drive Range Rover which got stuck on the beach. John didn't say a word between the time they arranged for help to come and when the tow truck driver showed up. Later asked why he was so quiet, John responded that he "was trying to think of something memorable to say to the tow truck driver because that's what people expected from him and word would get around." Original in safe.